Community-Based Development of UMKM in Cihanyawar Village: Collaborative Approaches to Packaging, Marketing, and Halal Certification - Al-Ghifary, Ariq; Fazriah, Siti; Maulida, Yuniar; Ratu, Mutiara; Meida, Puput; Ivanka, Rika; Hasmi, Syifa; Devi, Sri; Rizki, Muhamad; Nugraha, Derry (PT Agung Media Publisher, 2025)
This community-based development initiative focused on empowering local Micro, Small, and Medium Enterprises (UMKM) in Cihanyawar Village through collaborative strategies targeting three key areas namely packaging improvement, marketing enhancement, and halal certification facilitation. Employing a community-based research (CBR) framework, the program engaged 25 UMKM units spanning food processing, handicrafts, and agricultural products over a six-month intervention period. The initiative involved participatory training sessions, hands-on technical assistance, and sustained mentoring designed and implemented in collaboration with local stakeholders. Mixed-methods evaluation, including structured surveys, in-depth interviews, focus group discussions, and field observations, was conducted to assess outcomes before and after the intervention. Findings indicate substantial progress across all focus areas. Average packaging quality scores improved from 1.8 to 4.1 (127.8% increase), social media adoption reached 84%, and marketing channel diversity expanded by 240%. Halal certification efforts led to a 52% success rate among participating businesses. These outcomes translated into meaningful economic impact, with average monthly revenue rising by 56.6% and customer reach growing by 111.9%. Statistical analysis confirmed the program’s effectiveness (p < 0.001) across key performance indicators. The collaborative and integrated nature of the intervention generated synergistic effects, demonstrating the value of localized, community-based empowerment approaches in strengthening rural UMKM resilience and competitiveness.